Description of Complementary Feeding Practice to Underweight Children Under Two Years Old in The Working Area of Puskesmas Kanor, Bojonegoro District - Ainun; Dian Shofiya; Mujayanto; Nuning Marina Pengge; Lee Shoo Thien (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Children under two years of age, are in a very important developmental period often referred to as the Golden Age. Child classified as Underweight based on anthropometry, measurements if their body weight for Age (BB/U) is between -3 SD <-2 SD. According to data from the Bojonegoro District Health Service. This study aims to describe complementary feeding practice to underweight children aged 6-24 months with in the working area of the kanor community health center. Research used an interview method with a questionnare for data collectin, A total of 41 children were selected through random sampling. The result showed that the age at first complementary feeding was correct in 68.4% of cases however, frequency 75.6%, amount 63.4%, texture 75.6%, variation 53, 6%, responsiveness 58.5% and hygiene 58.5%. While most children had a story of exclusive breastfeeding, aspect such as children had a history of exclusive breasfeeding aspect such as frequency, quantity, texture, variety, and responsivenness of complementary feeding were incorrect even though cleanliness was satisfactory. Educational interventions are needed to improve knowledge and practices related to proper complementary feeding for children.